2020
DOI: 10.1186/s12883-020-02025-3
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: Dual versus mono antiplatelet therapy for acute non- cardio embolic ischemic stroke or transient ischemic attack, an efficacy and safety analysis - updated meta-analysis

Abstract: This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12883-020-02025-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Although most studies showed some increase in bleeding risk with DAPT, this was offset by the stroke prevention benefit if limited to short-term use. 795,796,806…”
Section: Management By Etiologymentioning
confidence: 99%
“…Although most studies showed some increase in bleeding risk with DAPT, this was offset by the stroke prevention benefit if limited to short-term use. 795,796,806…”
Section: Management By Etiologymentioning
confidence: 99%
“…Prospective randomized controlled trials showed that aspirin combined with clopidogrel reduced neurological deterioration in acute noncardiac stroke 54,55 . A meta-analysis of 16 randomized controlled trials involving 28,032 patients showed that dual antiplatelet therapy was superior to monoantibody platelet therapy in reducing the morbidity and mortality of stroke and its combined events (ie, cardiovascular disease), with no significant increase in bleeding events 56 …”
Section: Discussionmentioning
confidence: 99%
“…54,55 A meta-analysis of 16 randomized controlled trials involving 28,032 patients showed that dual antiplatelet therapy was superior to monoantibody platelet therapy in reducing the morbidity and mortality of stroke and its combined events (ie, cardiovascular disease), with no significant increase in bleeding events. 56 Using this nomogram to predict unfavorable outcomes in ischemic stroke patients 72 hours after intravenous thrombolysis is easy. For example, the score for a patient aged 70 years is 40 points.…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel is a platelet membrane adenosine diphosphate receptor inhibitor that effectively inhibits the generation of adenosine diphosphate, blocks platelet aggregation and binding to adenosine diphosphate, and activates and amplifies already aggregated platelets and adenosine diphosphate [19]. The combined use of these two drugs can further promote thrombus dissolution, inhibit platelet aggregation and adhesion, and thereby prevent thrombus formation [20]. Studies have confirmed the superior effectiveness and safety of dual antiplatelet therapy compared to monotherapy.…”
Section: Discussionmentioning
confidence: 99%